Formulasi dan Karakterisasi Minyak Atsiri Pala (Myristica fragrans) di Dalam Sistem Nanostructured Lipid Carrier - Satrialdi, Satrialdi; Fadilah, Alinda Nur; Rahma, Annisa (School of Pharmacy Institut Teknologi Bandung, 2025)
Essential oil extracted from nutmeg (Myristica fragrans) contains various beneficial compounds that can be used in medicines and cosmetics. Nevertheless, nutmeg essential oil (NEO) use in pharmaceuticals is limited by its high lipophilicity and tendency to degrade. Encapsulating NEO into a nanostructured lipid carrier (NLC) can be an alternative to overcome these problems. Thus, this study aimed to develop an NEO formula in an NLC system (NEO-NLC) for topical use, to characterize NEO-NLC, and to elucidate its potential as an antioxidant. The optimization of the NEO-NLC formula included selecting liquid lipid components, adjusting their ratios, choosing a sonicator, selecting a surfactant system, and optimizing sonication amplitude. The optimum NEO-NLC formula was then characterized by determining particle size and distribution, measuring zeta potential, estimating encapsulation efficiency, and evaluating antioxidant activity. The optimum NEO-NLC formula was obtained with a composition of 1.8% cetyl alcohol, 3.0% almond oil, 1.2% NEO, 3.2% Tween 80, 0.8% Plantacare® 1200, and demineralized water. The resulting NEO-NLC exhibited a particle size of 124.4 ± 4.7 nm, a polydispersity index of 0.35 ± 0.05, a zeta potential of -39.0 ± 3.6 mV, and an encapsulation efficiency of 95.3 ± 0.6%. Encapsulation of NEO into an NLC system resulted in a 2.9-fold increase in antioxidant activity compared to unencapsulated NEO. The developed NEO-NLC showed potential for pharmaceutical or cosmetic raw material use.